Corruption, Income Inequality and Human Resource Development in Developing Economies - Khan, Rana Ejaz Ali; Naeem, Hafiza Maria (Asian Journal of Economic Modelling, 2020)
This study examines the relationship between corruption, income inequality and human resource development by using simultaneous-equation model for a panel of 38 developing countries for the time period 2000-2015. The endogenous variables of human resource development, income inequality and corruption are measured by human resource development index, control of corruption index and Gini coefficient. The three stage least square results indicate that human resource development in negatively influenced by corruption and income inequality. Income inequality is positively affected by corruption and negatively by human resource development. On the other hand corruption is negatively influenced by human resource development and positively by income inequality. Among this troika of indicators corruption and income inequality are helping each other to resist human resource development. In the instrumental variables the urbanization, health expenditures and economic freedom positively contribute in human resource development. For developing economies it is needed to tackle the problem of corruption and income inequality for accelerate the human resource development.